INVOLVEMENT AND FORMATION OF PARISH PASTORAL COUNCIL OFFICERS IN THE EASTERN VICARIATE OF THE ARCHDIOCESE OF CAPIZ - Anoche, Menard Amongo (IDEAS: Journal of Management & Technology, 2025)
The church is facing challenges due to the growing secularization of society, leading to a decline in religious influence and participation. The Parish Pastoral Council plays a vital role in the Catholic Church, assisting the priest in fostering an active and enthusiastic parish community. The council's effectiveness depends on active involvement and quality formation from the parish. The study aimed to assess the level of involvement in doctrine, worship, and values, as well as the extent of formation in didache (teachings), koinonia (community), and diakonia (service) of 180 randomly selected parish pastoral council officers in the Eastern Vicariates of the Archdiocese of Capiz. A validated and reliability-tested researcher-made questionnaire was used to gather the data on the socio-demographic profile of the respondents; the level of involvement and the extent of formation of parish pastoral council officers. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, ANOVA, and Pearson-r. Utilizing the quantitative research design, the results revealed that the level of involvement and the extent of formation of the parish pastoral council officers was “high". The respondents' overall degree of involvement and formation was rated as "high", and when viewed collectively had the same "high level" observed in doctrine, worship, values, didache (teachings), koinonia (community), and diakonia (service). However, doctrine and didache (teachings) are the lowest among the variables of involvement and formation. The parish priest should prioritize and emphasize doctrinal formation for the council members. This can be done through workshops, study groups, and inviting guest speakers to provide in-depth teachings on Church doctrines.